Topological Indices for Inverse Graphs Associated With Finite Cyclic Group - Gopinath, S.; Doss, A. Richard Praveen; Kalaimurugan, G. (Communications in Mathematics and Applications, 2023)
Topological indices are mathematical descriptors for molecular structures. These descriptors are used to describe physico-chemical properties such as solubility, molecular shape and molecular weight. In this paper, we present distance-based topological indices such as Wiener index and hyper-Wiener index by using Hosoya polynomial for inverse graphs associated with finite cyclic group. Also, we have found eccentricity based topological index of inverse graphs associated with finite cyclic group.
Keywords: Hosoya polynomial; Wiener index; Hyper-Wiener index; Inverse graph